Pine Forest Management and Disturbance in Northern Poland: Combining High-Resolution 100-Year-Old Paleoecological and Remote Sensing Data - Łuców, Dominika; Lamentowicz, Mariusz; Kołaczek, Piotr; Łokas, Edyta; Marcisz, Katarzyna; Obremska, Milena; Theuerkauf, Martin; Tyszkowski, Sebastian; Słowiński, Michał (Frontiers in Ecology and Evolution, 2021)
Global warming has compelled to strengthen the resilience of European forests. Due to repeated droughts and heatwaves, weakened trees become vulnerable to insect outbreaks, pathogen invasions, and strong winds. This study combines high-resolution analysis of a 100-year-old high-resolution peat archive synthesized from the Martwe peatland in Poland with remote sensing data. We present the first REVEALS based vegetation reconstruction in a tornado-hit area from Poland on the background of previous forest management in monocultural even-aged stands – Tuchola Pinewoods. During the 20th century, the pine monocultures surrounding the peatland were affected by clear-cutting and insect outbreaks. In 2012, a tornado, destroyed ca. 550 ha of pine forest around the peatland. The palynological record reflects these major events of the past 100 years as well as changes in forest practices. Our study showed the strong relationships between the decrease of Pinus sylvestris (Scots pine) in palynological record as well as planting patterns after the tornado. Moreover, past forestry practices [such as domination of Pinus sylvestris, the collapse of Picea abies (Norway spruce), low share of Betula spec. (birch) due to Pinus sylvestris promotion and probable also to a lesser by removal of Betula as a “forest weed,” and low plant coverage of tree species due to clear-cutting and cutting after insect outbreaks] were well identified in the proxy record. In monocultures managed over decades, the reconstruction of vegetation may be challenging due to changes in the age composition of the Pinus sylvestris stands. We found that through historical, remote sensing, and paleoecological data, the dynamics of disturbances such as insect outbreaks and tornadoes, as well as the changing perceptions of local society about forests, can be determined.